2013
DOI: 10.4049/jimmunol.1202716
|View full text |Cite
|
Sign up to set email alerts
|

IL-22 Regulates Iron Availability In Vivo through the Induction of Hepcidin

Abstract: Iron is a trace element important for the proper folding and function of various proteins. Physiological regulation of iron stores is of critical importance for RBC production and antimicrobial defense. Hepcidin is a key regulator of iron levels within the body. Under conditions of iron deficiency, hepcidin expression is reduced to promote increased iron uptake from the diet and release from cells, whereas during conditions of iron excess, induction of hepcidin restricts iron uptake and movement within the bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 45 publications
(50 reference statements)
0
29
0
Order By: Relevance
“…5). A biologically significant contribution of Tyk2 to IL-22R signaling has also been found in murine keratinocytes (5) and hepatocytes (49). The antimicrobial proteins RegIIIb and RegIIIg are protective during colitis and have been previously described as direct targets of IL-22/STAT3 in colonic epithelial cells (35,40,50).…”
Section: Discussionmentioning
confidence: 93%
“…5). A biologically significant contribution of Tyk2 to IL-22R signaling has also been found in murine keratinocytes (5) and hepatocytes (49). The antimicrobial proteins RegIIIb and RegIIIg are protective during colitis and have been previously described as direct targets of IL-22/STAT3 in colonic epithelial cells (35,40,50).…”
Section: Discussionmentioning
confidence: 93%
“…Mechanistic experiments have demonstrated that IL-6 acts by binding to its receptor gp130 on hepatocytes, thereby activating signals that phosphorylate the transcription factor signal transducer and activator of transcription 3 (STAT3), which binds to the promoter of the hepcidin gene and increases its expression (15,23-25). Cytokines other than IL-6, such as IL-1 and IL-22, have been shown to be involved in hepcidin up-regulation in cultured cells and in mice, but the relevance of these observations to the pathophysiology of inflammatory states is yet to be determined (26-28). Tumor necrosis factor α (TNFα) is another cytokine that is often elevated in inflammatory conditions, but its role in hepcidin expression is unclear.…”
Section: Dysregulation Of Iron Metabolism By Inflammationmentioning
confidence: 99%
“…Smith et al [116] also backed this up, to suggest that IL-22 influences hepcidin production upon the activation of JAK2 and STAT3. Mouse who were injected with IgG1 Fc attached to the N-terminus of IL-22-an IL-22R agonist -were seen to have an increased expression of hepcidin and a subsequent decrease in the level of circulating serum iron.…”
Section: Il-22 As a Hepcidin Suppressormentioning
confidence: 99%
“…Based on this notion, IL-22 may be a new therapeutic target for cancer prevention, using an Ab-mediated blockade of JAK-STAT signalling. This Ab-blockade, while useful in cancer inhibition, also partially blocks hepcidin expression, thus, playing a role in the treatment of cancer-induced anaemia [116]. As well as its role in anaemia and iron overload disorder, IL-22 is thought to be protective against liver necrosis in mouse models [116].…”
Section: Il-22 As a Hepcidin Suppressormentioning
confidence: 99%